2017
DOI: 10.9767/bcrec.13.1.1226.24-35
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Alumina-Supported Ruthenium, Platinum, and Cobalt Nanoparticles towards the Oxidation of Cyclohexane to Cyclohexanol and Cyclohexanone

Abstract: A series of metal-loaded (Ru, Pt, Co) alumina catalysts were evaluated for the catalytic oxidation of cyclohexane using tertbutylhydroperoxide (TBHP) as oxidant and acetonitrile or acetic acid as solvent. These materials were prepared by the impregnation method and then characterized by Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES), H2 chemisorption, Fourier Transformed Infrared Spectroscopy (FTIR), High-Resolution Transmission Electron Microscopy (HRTEM), and X-ray Diffraction (XRD). All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The production of high-purity cyclohexane follows a two-stage scheme: in the 1 st stage, used Ni on the carrier (30-45% Ni/Al 2 O 3 ); In the 2 nd stage, Pt catalysts are used on the carrier (0.2-1.0% Pt/ Al 2 O 3 ). As a result, cyclohexane is obtained with a purity of 99.6-99.9% [64].…”
Section: Process Methods and Acquired Patentsmentioning
confidence: 99%
“…The production of high-purity cyclohexane follows a two-stage scheme: in the 1 st stage, used Ni on the carrier (30-45% Ni/Al 2 O 3 ); In the 2 nd stage, Pt catalysts are used on the carrier (0.2-1.0% Pt/ Al 2 O 3 ). As a result, cyclohexane is obtained with a purity of 99.6-99.9% [64].…”
Section: Process Methods and Acquired Patentsmentioning
confidence: 99%
“…Goodman [12] studied the catalytically active Au on TiO2, he found that strong metal-support interaction leads to the suppression of hydrogen (H2) and carbon monoxide (CO) chemisorptions for various metal and for active Au/TiO2 catalyst CO chemisorptions is enhanced due to electron transfer from TiO2 to Au. Catalytic properties of alumina supported ruthenium (Ru), platinum (Pt), and cobalt (Co) nanoparticles was also investigated by Rekkab-Hammoumraoui and Choukchou-Braham [13], they concluded that the support, the noble and the non-noble metals can be active for oxidation of cyclohexane and they found that Ru and Pt are in metallic form whereas Co is in the oxides form.…”
Section: Introductionmentioning
confidence: 99%